Seventh Five Year Plan 1985-90 Mid Term Appraisal - Planning Commission, Government of India (Planning Commission, Government of India, 1985)
In the first two years of the plan the pace of public investment has been maintained at the required level. Infrastructural constraints have been lightened and industrial growth has been sustained at unprecedently high levels for three years running. Anti-poverty and employment programmes have been generally strengthened and human resource development has been given new direction with the new National Policy on Education.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Seventh Five Year Plan- India; Economic development and growth